Developing Mobile Learning Media as an Interactive Learning Innovation in Qur'anic Kindergarten Education - Muhammad Fauzi; Ahir Yugo Nugroho Harahap (Jurnal Penelitian Samudra, 2026)
The rapid advancement of digital technology has transformed educational practices, including early childhood Islamic education. However, learning activities in many Qur'anic Kindergartens (TK Al-Qur'an) continue to rely on conventional teaching methods and printed learning materials, resulting in limited student engagement and interactive learning experiences. This study aims to develop a mobile learning media as an interactive learning innovation to improve learning engagement and learning achievement among children in Qur'anic Kindergarten education. The research employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. The developed application integrates interactive multimedia features, including animated Arabic letters (Hijaiyah), audio recitation (Murottal), educational games, formative quizzes, progress tracking, and visual storytelling designed according to early childhood learning characteristics. The product was validated by experts in instructional media, early childhood education, and Islamic education before being implemented with 60 kindergarten students and six teachers at TK Al-Qur'an Taqarub. Data were collected through expert validation questionnaires, the System Usability Scale (SUS), classroom observations, learning engagement questionnaires, and pretest-posttest assessments. Descriptive statistics, normalized gain (N-Gain), paired-sample t-tests, and qualitative feedback analysis were employed to evaluate the effectiveness of the developed media. The findings indicate that the mobile learning media achieved a high level of content validity and usability, with an average expert validation score exceeding 90% and an SUS score categorized as excellent. Students demonstrated significantly higher learning achievement and engagement after using the application, with a moderate-to-high N-Gain score and statistically significant improvements (p < 0.05). Teachers also reported increased classroom interaction, learner motivation, and efficiency in monitoring students' learning progress. The study concludes that mobile learning media provides an effective and innovative solution for enhancing interactive learning in Qur'anic Kindergarten education by combining Islamic learning content with child-centered digital pedagogy. The developed application contributes to the growing body of knowledge on mobile-assisted early childhood education and offers practical implications for integrating digital technology into Islamic educational institutions.